Calculation of parameters of balancing devices for traction substation of alternative current with visual simulation - Ягуп, Валерий Григорьевич; Ягуп, Екатерина Валериевна (Eastern-European Journal of Enterprise Technologies, 2014)
Traction substation with the star - delta connection of transformer windings is considered. Power supply of traction load is carried out from one side of the triangle on the secondary side of the transformer, which creates an unbalance in the power supply system. In turn, current and voltage unbalance reduces the power factor for power sources in each phase and increases losses in the transmission line. The study of electromagnetic processes, conducted using the developed visual model has confirmed the presence of a substantial unbalance in the system. With the help of the visual model and search engine optimization, parameters of balancing device, consisting of reactive elements are found. Herewith, currents in transformer lines and windings are balanced, and reactive power in the power supply system is fully compensated. Due to the perfect balancing and full compensation of reactive power, the losses in the system are minimized.